2020
DOI: 10.3390/cells9051082
|View full text |Cite
|
Sign up to set email alerts
|

The Lysosomotropic Activity of Hydrophobic Weak Base Drugs is Mediated via Their Intercalation into the Lysosomal Membrane

Abstract: Lipophilic weak base therapeutic agents, termed lysosomotropic drugs (LDs), undergo marked sequestration and concentration within lysosomes, hence altering lysosomal functions. This lysosomal drug entrapment has been described as luminal drug compartmentalization. Consistent with our recent finding that LDs inflict a pH-dependent membrane fluidization, we herein demonstrate that LDs undergo intercalation and concentration within lysosomal membranes. The latter was revealed experimentally and computationally by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 119 publications
2
38
0
Order By: Relevance
“…According to recent data, LA weak bases modify pH-dependent membrane fluidization and undergo intercalation and concentration within the lysosomal membrane. The latter phenomenon has been proven experimentally (as increased free activity of lysosomal enzymes, such as acid phosphatases in lysosomes, in comparison with no-treatment controls), by morphological methods with the help of confocal microscopy involving fluorescent compounds, and by means of drugs delivered inside the lysosomal membrane, followed by molecular dynamics modeling of the pH-dependent membrane insertion and accumulation of various LA weak bases, including some anticancer drugs [49].…”
Section: Low-molecular-weight Weak Bases In Experimental and Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent data, LA weak bases modify pH-dependent membrane fluidization and undergo intercalation and concentration within the lysosomal membrane. The latter phenomenon has been proven experimentally (as increased free activity of lysosomal enzymes, such as acid phosphatases in lysosomes, in comparison with no-treatment controls), by morphological methods with the help of confocal microscopy involving fluorescent compounds, and by means of drugs delivered inside the lysosomal membrane, followed by molecular dynamics modeling of the pH-dependent membrane insertion and accumulation of various LA weak bases, including some anticancer drugs [49].…”
Section: Low-molecular-weight Weak Bases In Experimental and Clinicalmentioning
confidence: 99%
“…Low-molecular-weight lysosomotropic lipophilic weak bases (e.g., CQ and its analogs and some antitumor drugs) [1], undergo marked sequestration and concentration within lysosomes, thereby changing lysosomal functions [49]. Additionally, studies have revealed increased sensitivity of cancer cells to certain LA and suggested that the actions of LA may potentially represent a promising approach for selective destruction of cancer cells.…”
Section: Low-molecular-weight Weak Bases In Experimental and Clinicalmentioning
confidence: 99%
“…Various lipid molecules can then be considered as a potential representative to analyze Ves a 1 binding towards a phospholipid molecule. However, in this study, 1,2-Dimyristoyl-sn-glycero-3-phosphorylcholine (DMPC) was chosen as a lipid representative since DMPC could well represent the phospholipid bilayer in both computational and experimental studies [14][15][16][17][18]. In this study, the lipid was docked into the 200-ns snapshot of Ves a 1 and the binding energy as well as conformation was obtained using SwissDock.…”
Section: Ves a 1 Auxiliary Binding Site Identification And Interactiomentioning
confidence: 99%
“…Among the most prominent sites for lysosomal protonation are basic amine centers as, for example, contained in conventional anti-malarials, such as chloroquine and hydroxychloroquine [106]. Computer simulation has shown that the protonated portion of these aminic compounds localizes just beneath the phospholipid head groups of the lysosomal membrane and become entrapped within the luminal lysosome as the energetic barrier for charged molecules to diffuse across the lipid bilayer out to the cytosol is insurmountable under physiological settings [107]. Coincidentally, staggering numbers of aminic chemotherapeutic agents (e.g., chlorambucil, cyclophosphamide, lomustine, and doxorubicin) are susceptible to protonation and, thus, inevitably confer varying degrees of lysosomotropism due to the fact weakly basic compounds often are the predominant drug presentation following optimization of drug bioavailability and pharmacokinetic parameters.…”
Section: Lysosomal Entrapment Of Weak-base Compoundsmentioning
confidence: 99%